An Analysis Of Online Learning Media Functions In The Era Of The Covid-19 Pandemic (Qualitative Descriptive Study On Grade 6 Students At Sdn 06 Bengkulu Tengah) - Powandi, Okta; Yanto; Sari , Sapta (Multidisciplinary Journals, 2024)
The COVID-19 pandemic requires online learning at SDN 06 Bengkulu Tengah. Therefore, this study discusses the analysis of the function of online learning media in the era of the covid-19 pandemic on class 06 students at SDN 06 Bengkulu Tengah. The informants in this study were 4 teachers. Data collection techniques used in this study were interviews, observation, and documentation. The data were analyzed using qualitative descriptive analysis techniques and used the theory of Sanjaya (2012) about 4 functions of online learning media including the communicative function, the motivation function, the perception equalization function and the individuality function. The results of research show that; the communicative function, the teacher provides material in various ways so that students' understanding of speaking in public places and working together with others is getting better. the motivational function, the teacher does it by providing material and entertainment in the form of videos, so that students do not get bored and get their own motivation in watching and listening to the material. The meaningful function of using the teacher's media not only increases the addition of information, but can increase students' ability to analyze and create, the function of equalizing this perception is not only done by the teacher but also to the guardians of students through meetings in providing information about online learning, the function of individuality in the interests of each style. Different students, each teacher is required to be able to unify the understanding of the same information and material even though the interests of different learning styles are different.